THE INFLUENCE OF BRAND AWARENESS AND DIGITAL MARKETING ON PURCHASING DECISIONS AT DW DIGITAL PRINTING - Agus Kurniawan; Gian Fitralisma; Hartanto Halim (PT. Berkah Digital Teknologi, 2025)
Purpose: This study aims to determine the extent to which brand awareness and digital marketing influence consumer purchasing decisions at DW Digital Printing, Majalengka Regency. Research Methodology: This study employed a quantitative research design using a survey method. Data were collected through Google Form questionnaires distributed to DW Digital Printing consumers. The population consisted of 211 respondents, with a sample size of 67 respondents selected using a simple random sampling technique. The data were analyzed using multiple linear regression analysis with SPSS software, including t-test and F-test for hypothesis testing. Results: The findings indicate that brand awareness has a positive and significant effect on purchasing decisions (t = 2.071 > 1.669; p = 0.04 < 0.05) with a contribution of 59%. Similarly, digital marketing has a positive and significant effect (t = 0.108 > 1.669; p = 0.03 < 0.05) with a contribution of 61%. Simultaneous testing shows that both variables jointly have a positive and significant effect of 92% on purchasing decisions (F = 4.350 > 2.39; p = 0.01 < 0.05). Limitations: This study focuses only on DW Digital Printing in Majalengka Regency and may not represent other regions or industries. The sample size was relatively small and limited to one business unit. Contribution: This study contributes to the fields of marketing management and digital business strategy, especially in understanding how brand awareness and digital marketing influence consumer behavior in the digital printing industry and SMEs in Indonesia.